Selection of IBM population inbred lines with improved root architectural traits and stem diameter that can enable them to tolerate nitrogen and phosphorus stresses - Shaku, Manchidi Melda (My University, 2018)
Two experiments were conducted at Ukulima Root Biology Centre, Waterberg district in Limpopo Province (24°32'58.1"S, 28°06'21.1"E) during 2013-2014 cropping season to select IBM population inbred lines with improved root whorl and stem diameter that can enable them to tolerate nitrogen and phosphorus stress. The experiments were laid out in a Split plot format based on a randomized complete block design with four replicates. The main plot factors were: nitrogen levels (low and high) and phosphorus (low and high), in the respective trials and maize inbred lines (MO345, MO034, MO001, MO199, MO031 and MO196) were in the sub plots. Traits investigated included shoot morphological traits (plant height, leaf area per plant, chlorophyll content, stem diameter, number of leaves), root architectural traits (Whorl angles, root area, average root density, number of adventitious roots, number basal roots, average lateral root length, lateral branching frequency, root top angle, root bottom angle, distance to the first lateral root) and dry biomass. Results showed morphological traits, root architectural traits and biomass were affected by nitrogen fertilizer. Those traits were greater under high nitrogen level. On the other hand nitrogen had no influence on stem diameter size variation and whorl distribution. Plant height, number of leaves and dry biomass were significantly different among the inbred lines. The interaction of inbred and nitrogen fertilizer level had significant effect on leaf width and leaf area per plant. The lowest leaf width was recorded on inbred MO345 under low nitrogen level, while the highest value was recorded on inbred MO345 under high nitrogen level. Inbred MO031 and MO199 had highest values of leaf area per plant under high nitrogen level and inbred MO345 had the lowest value under low nitrogen level. Inbred lines planted under high nitrogen level had relative advantage in leaf growth over inbred lines planted under low nitrogen level. The study showed that nitrogen fertilizers have positive effect on some root architectural traits and growth parameters of maize. Maximum leaf area was obtained by inbred MO031 and MO199 under high nitrogen level. Thus, in order to enhance leaf growth and physiological traits, the use of either MO031 or MO199 is recommended under high nitrogen level while any of these inbred lines MO001, MO034 or MO199 can be used under low nitrogen production as they are highly tolerant to low soil xiv nitrogen. Morphological and root architectural traits correlated positively with dry biomass in both low and high N level. Results from the phosphorus split plot showed that only projected root area was affected by phosphorus level. Chlorophyll content, plant height, 1st whorl angle, 4th whorl angle, root top angle, root bottom angle, average lateral root length and lateral branching frequency differed significantly among the inbred lines. The interaction effect of phosphorus and inbred on root top angle and average lateral root length was significant. Inbred MO199, inbred MO034 and MO031 recorded the shallowest angles under low and high phosphorus level respectively, while inbred MO345 recorded the steeper root top angle at 54.44° under high phosphorus level. Thus to enhance P uptake, inbred MO199 is a potential candidate on low P soils. To improve water and N acquisition efficiency inbred MO345 with high phosphorus level can be used, therefore MO345 with high phosphorus can be recommended for water scarce areas such as Limpopo province. Inbred MO199 had the longest lateral roots of 251.46 mm under lower P level and significantly longer than inbred MO199 and MO001 both at lower phosphorus level. Inbred MO345 (182.88 mm) and MO001 (179.22 mm) were highly tolerant to the low P conditions as the two had shorter lateral roots, a trait vital for uptake of P. Inbred MO199 (251.46 mm) had the longest lateral roots under low P conditions showing higher tolerance to low P conditions. There were positive and significant correlations between dry biomass and morphological traits and root architectural traits on both low and high phosphorus levels. A strongly negative correlation was however observed between biomass and 2nd whorl angle on high phosphorus level. The high significant correlations indicate that selection of high yielding inbreds may be useful based on phosphorus level and biomass. This study showed that several traits have potential under low N and P levels, hence they can be used as selection criteria for inbred lines with improved nutrient use efficiency. Keywords: Maize inbred lines, fertilizer, growth, correlation, root angles
Thesis (M.Sc. Agric. (Agronomy)) --University of Limpopo, 2018
Keywords: Maize inbred lines; Fertilizer; Growth; Correlation; Root angles; Agronomy; Corn as seed